IFPRI’s research in fragile and conflict-affected settings - Kosec, Katrina; Carrillo, Lucia (International Food Policy Research Institute, 2025)
IFPRI’s research provides partners with support through a wide range of evidence and products: Decision-support tools spanning all phases of crisis and conflict: anticipating and preventing risks before they escalate, monitoring and responding during acute crises, and supporting long-term recovery and resilience. Context-relevant evidence on policies, programming, and interventions to address the unique challenges faced by FCAS—relevant for governments, UN agencies, NGOs, and other partners. Rapid-response policy support to address emerging challenges. Best-practice guidance for conflict-sensitive, gender-responsive policy designs.